AN EVIDENCE BASED REVIEW ON THE ROLE OF AYURVED IN GERIATRIC CARE (AYUSHDHARA, 2020)
Ageing is a constant, irreversible, unstoppable and natural physiological process. It is considered to be the most crucial time period of life as the physical strength in this period declines gradually. Many physical and psychological problems start surfacing, and dependency on others increases. Due to increased incidences of such problems in elderly, there is a need of time to understand the importance of geriatrics globally. That’s why geriatrics is now a very speedily emerging branch of research in the present era. Ayurved, having a holistic approach towards health, has a great potential to do prevention of ageing process and related diseases. Ayurved, the science of life has a separate branch named Jara or Rasayan to deal with the diseases of old people and to delay the ageing process. Ayurved also suggests lifestyle measures, dietetics, Panchkarma therapies, Yoga along with Rasayan to delay the process of ageing and to improve the quality of life of geriatric group of people. That is why there is a need of large scale research in this field to prepare a complete holistic approach evidence based treatment protocol for geriatric people. Thus, the topic is chosen to review the concept of ageing based on both Ayurvedic and modern concept, problems of the old age people, complete comprehensive assessment of old people, old researches on geriatrics and clinical realities which makes geriatric research difficult. This review will help to initiate future Ayurved based research protocol.